NanoSPECT imaging reveals the uptake of 123I-labelled oxidized low-density lipoprotein in the brown adipose tissue of mice via CD36. Issue 4 (21st October 2022) - Hosomi, Kento; Kawashima, Hidekazu; Nakano, Atsushi; Kakino, Akemi; Okamatsu-Ogura, Yuko; Yamashita, Yuki; Sasaoka, Mai; Masuda, Daisaku; Yamashita, Shizuya; Chen, Chu-Huang; Yuzuriha, Shunsuke; Hosoda, Hiroshi; et al.
Abstract: Aims: The liver is the major organ shown to remove oxidized low-density lipoprotein (oxLDL) from the circulation. Given increased evidence that thermogenic adipose tissue has anti-effects, we used 123 I-labelled oxLDL as a tracer to reveal oxLDL accumulation in the brown adipose tissue (BAT) of mice. We also explored the mechanisms of oxLDL accumulation in BAT. Methods and results: We used high-resolution nanoSPECT/CT to investigate the tissue distribution of 123 I-oxLDL and 123 I-LDL (control) following intravenous injection into conscious mice. 123 I-oxLDL distribution was discovered in BAT at an intensity equivalent to that in the liver, whereas 123 I-LDL was detected mostly in the liver. Consistent with the function of BAT related to sympathetic nerve activity, administering anaesthesia in mice almost completely eliminated the accumulation of 123 I-oxLDL in BAT, and this effect was reversed by administering β3 -agonist. Furthermore, exposing mice to cold stress at 4°C enhanced 123 I-oxLDL accumulation in BAT. Because in 123 I-oxLDL, the protein of oxLDL was labelled, we performed additional experiments with DiI-oxLDL in which the lipid phase of oxLDL was fluorescently labelled and observed similar results, suggesting that the whole oxLDL particle was taken up by BAT. To identify the receptor responsible for oxLDL uptake in BAT, we analysed the expression of known oxLDL receptors (e.g. SR-A, CD36, and LOX-1) in cultured brown adipocyte cell line and primary brown adipocytes and found that CD36 was the major receptor expressed. Treatment of cells with CD36 siRNA or CD36 neutralizing antibody significantly inhibited DiI-oxLDL uptake. Finally, CD36 deletion in mice abolished the accumulation of 123 I-oxLDL and DiI-oxLDL in BAT, indicating that CD36 is the major receptor for oxLDL in BAT. Conclusion: We show novel evidence for the CD36-mediated accumulation of oxLDL in BAT, suggesting that BAT may exert its anti-atherogenic effects by removing atherogenic LDL from the circulation. Graphical Abstract: Graphical Abstract Visualization of brown adipose tissue (BAT) with nanoSPECT after the intravenous injection of a 123 I-labelled oxidized low-density lipoprotein (oxLDL) probe ( 123 I-oxLDL). Intravenously injected 123 I-oxLDL accumulated in BAT at a high density similar to that in the liver, whereas the control 123 I-labelled LDL probe accumulated mostly in the liver. Stimulation of BAT by β-3 agonist and cold stress enhanced 123 I-oxLDL accumulation in BAT. In contrast, anaesthesia suppressed the accumulation of 123 I-oxLDL in BAT. Deleting CD36 in mice completely abolished the accumulation of 123 I-oxLDL in BAT, indicating that CD36 is the receptor that mediates oxLDL uptake in BAT. These data support a possible role of BAT in protecting against atherosclerosis.